2012
DOI: 10.5455/msm.2012.24.162-164
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks in Medical Education in Bosnia and Herzegovina

Abstract: Introduction:Beginning with the late twentieth and early twenty-first century, the Internet was a significant additional tool in the education of teenagers. Later, it takes more and more significant role in educating students and professionals.Goal:The aim of this paper is to investigate, to what extent and how effectively the Internet is used today by students of biomedical faculties in Bosnia and Herzegovina. In addition, more specifically, this paper will research the implications of the well-known social n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 4 publications
0
22
0
Order By: Relevance
“…It could be concluded that, attitude of the students towards research is partial, therefore, gender, age and education level have no effect on the attitude of the students to research (16, 17). In other words, attitudes towards research is influenced by the other variables (5, 12, 18-20). …”
Section: Discussionmentioning
confidence: 99%
“…It could be concluded that, attitude of the students towards research is partial, therefore, gender, age and education level have no effect on the attitude of the students to research (16, 17). In other words, attitudes towards research is influenced by the other variables (5, 12, 18-20). …”
Section: Discussionmentioning
confidence: 99%
“…Following the previous statements the social networks can be divided into several groups, depending on connection methods, field of operations or expertise of those who participate in specific networks (6, 7):…”
Section: Biomedical Scientific Research Systemsmentioning
confidence: 99%
“…Progressive expansion of biomedical documents and information and technological advances require even better selection of data and information retrieval in order to achieve better application of scientific information. This goal is accomplished by use of world’s databases (3, 4, 7). …”
Section: Research Systems For Cataloging (Biomedical Literature Damentioning
confidence: 99%
“…In this regard, some have proposed that platforms of post-publication peer review may provide the required safeguard in this new setting 22. In addition, intuitive browsing of journal content on smartphones and the iPad is being provided by a growing number of publications (including the European Heart Journal )24 25 to enhance diffusion of contents 21. Furthermore, some Web 2.0 technologies facilitate collaborative data collection for clinical trials 23.…”
Section: Electronic Editions and The Internet: A Paradigm Shift In Scmentioning
confidence: 99%